1984
DOI: 10.1037/0033-2909.96.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Generality of free-operant avoidance conditioning to human behavior.

Abstract: The generality of free-operant avoidance conditioning between human and nonhuman behavior is reviewed. The following five topics are examined: (a) response acquisition, (b) response maintenance, (c) extinction, (d) exteroceptive stimuli, and (e) pharmacological agents. The results from research with humans are compared and contrasted with those from nonhumans. Following this, the differences between human and nonhuman behavior on avoidance schedules are related and compared with those identified for humans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 88 publications
2
25
0
Order By: Relevance
“…Second, extending the observational phase to include modeling of unsignaled US presentations prior to a reinstatement test phase would be a novel synthesis of observational-learning of avoidance with human reinstatement research and allow for the detection of potentially transient effects on generalization. Third, exposing participants to a movie where the US is removed (extinction) or where the avoidance response is prevented and the US presented independent of responding (Higgins and Morris, 1984) would permit an examination of the relative effectiveness of these separate, operant extinction methods. Moreover, effects of presenting either the generalized or learned cues in tandem with these extinction methods could be tested and applied to analog analyses of exposure-based therapy for reducing levels of problematic avoidance that is often seen in anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Second, extending the observational phase to include modeling of unsignaled US presentations prior to a reinstatement test phase would be a novel synthesis of observational-learning of avoidance with human reinstatement research and allow for the detection of potentially transient effects on generalization. Third, exposing participants to a movie where the US is removed (extinction) or where the avoidance response is prevented and the US presented independent of responding (Higgins and Morris, 1984) would permit an examination of the relative effectiveness of these separate, operant extinction methods. Moreover, effects of presenting either the generalized or learned cues in tandem with these extinction methods could be tested and applied to analog analyses of exposure-based therapy for reducing levels of problematic avoidance that is often seen in anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, we employed a stringent avoidance conditioning criterion similar to that adopted by previous studies (Dymond et al, 2007 in which a minimum of six consecutive avoidance responses to AV2 were required. This emphasis on maintenance of response rate, set within a predetermined maximum number of avoidance trial exposures, maintained avoidance under free-operant conditions (Higgins & Morris, 1984). This was necessary in order to present multiple stimulus probes during the critical testing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present results suggest that Laties and Weiss' (1966) earlier demonstration of environmental modulation of the behavioral effects of scopolamine in pigeons has generality to other anticholinergics and, more important, to human behavior maintained under complex reinforcement contingencies. It is important to note that although attention is often directed at the discrepancies between human and nonhuman operant behavior in laboratory settings, there has also been a great deal of generality demonstrated that should not be overlooked (e.g., Griffiths, Bigelow, & Henningfield, 1980;Higgins & Morris, 1984;Higgins et al, 1987).…”
Section: Discussionmentioning
confidence: 99%